Bio Synthesis of Copper oxide Nanoparticles from Jatropha Curcas Leaf Extract and Their Antibacterial Activity Study - Al Mazroui Mallak Mohammed Sarahan; Devi Geetha; Al Abdali Anwar Mohammed Ali Hamed; Al Alawi Sultan Majid Khalfan (BIO Web of Conferences)
Ecofriendly and cost effective technologies in the synthesis of nanomaterials are receiving special attention due to their wide range of applications in environmental remediation, medicine, and bio sensing. Green nanotechnology has emerged as a novel scientific research in the synthesis of nanoparticles by a simple, cost effective and ecofriendly manner. The current research focused on the green synthesis of copper oxide nanoparticles employing environmentally friendly and sustainable technique using Jatropha curcas leaf extract as reducing and capping agents. The synthesized nano particles were analyzed by Fourier Transform Infrared Spectroscopy (FT-IR), X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), and Energy Dispersive X-Ray (EDX) analysis. The fabricated nanoparticles were successfully employed in the antibacterial activity study by disc diffusion technique. The green synthesized copper oxide nanoparticles showed excellent antibacterial activity.